Tunjungan Loop sebagai Strategi Penguatan Employee Engagement dan Kesehatan Kerja: Studi pada BRI Regional Office Surabaya - Rosianawati, Nabilah (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to examine the role of the Tunjungan Loop program as a strategic initiative to strengthen employee engagement and occupational health at BRI Regional Office Surabaya. Tunjungan Loop is a routine physical activity program conducted every Tuesday and Friday at 5:30 AM, involving rotating responsibilities among 24 branch offices under the regional coordination. The study employs a descriptive qualitative approach, using semi-structured interviews and direct observation as data collection methods. The findings reveal that the program enhances employee engagement across emotional, cognitive, and physical dimensions, while also fostering a healthier, more collaborative, and dynamic work environment. Furthermore, the program promotes organizational culture through inter-branch interaction and participative leadership. Nonetheless, challenges such as unequal participation, logistical constraints, and the need for activity variation must be addressed to optimize its impact. With continuous improvement, Tunjungan Loop holds significant potential as a holistic organizational initiative focused on employee well-being and engagement.